Copyright Infringement in Indonesia: Applicable Sanctions and Legal Procedures - Solihan Makruf; Rizal Agung Mufti; Radja Haehta Sembada; Iqbal Taufik Maulana; Muhamad Kholid (Fakultas Syariah IAIN Langsa, 2026)
Ideally, copyright, as part of intellectual property rights, should receive full protection from the state through firm and effective legal instruments. Law Number 28 of 2014 concerning Copyright provides a clear legal framework to ensure such protection. However, in reality, copyright infringement remains widespread in Indonesia, taking forms such as piracy, unauthorized use, and illegal distribution through digital platforms. This condition highlights a gap between the ideal legal norms and their implementation in practice. This study aims to analyze the sanctions and legal processes applicable to copyright infringement in Indonesia and evaluate the effectiveness of their implementation based on the existing laws and regulations. The methodology used in this research is a normative juridical approach, with primary data sources consisting of statutory regulations, academic literature, and relevant court decisions. The findings indicate that although Indonesia has relatively comprehensive regulations on copyright, the implementation of sanctions and legal procedures still faces obstacles, such as weak law enforcement, low public awareness, and the challenges of digitalization that facilitate the rapid spread of infringement. Therefore, a synergistic effort among policymakers, law enforcement authorities, and society is needed to build an effective and adaptive copyright protection system in response to contemporary developments.